Free Radical Scavenging Activities of the Extracts from Lysimachia foenum-graecum Hance - Yi, Xianghui; Zou, Biqun; Zhang, Ye; Liu, Xianxian; Wang, Hengshan (Asian Journal of Chemistry, 2011)
Under ultrasound, Lysimachia foenum-graecum Hance herbs were extracted with ethanol to offer concrete and oil. The free radical scavenging activities of concrete and oil were evaluated against DPPH, ABTS, hydroxyl and superoxide anion radicals, respectively. It can be found that both of concrete and oil show good radical scavenging activities, while oil is superior to concrete. It is a pity that both of concrete and oil show less scavenging activity than BHT in DPPH and ABTS assay with IC50 44.3 and 29.5 μg/mL, respectively.